Developing and Evaluating Content-Based Virtual Reality for Improving Learning Effectiveness in IT Education - Jasruddin; Ridwan Daud Mahande; Kurnia Prima Putra (Jurusan Teknik Informatika dan Komputer, 2025)
Undergraduate Information Technology (IT) education often faces challenges in delivering complex instructional materials that are difficult for students to understand using conventional learning methods. Technology-based visualization, particularly Virtual Reality (VR), has a significant potential to enhance conceptual comprehension by offering immersive and interactive learning experiences. This study aims to develop Content-Based Virtual Reality (CBVR) and evaluate its effectiveness in supporting the learning of desktop PC hardware introduction. A research and development (R&D) approach was implemented by adapting the Alessi and Trollip model, which consists of planning, design, and development stages. Expert validation was conducted to assess the accuracy and quality of the content, while practicality and effectiveness tests involved students from the Informatics and Computer Engineering Education program. Data were gathered through questionnaires and observations and analyzed using descriptive statistics from Jamovi. The findings showed that the developed CBVR content is valid, feasible, and capable of providing a more engaging and immersive learning environment. The effectiveness results indicate a notable improvement in students’ understanding compared to conventional learning approaches, reflected in increased learning scores and higher engagement levels. CBVR has proven effective in enhancing both conceptual and procedural understanding and holds strong potential for broader application in undergraduate IT education.